Current management of anal fistulas in Crohn’s disease - Hermann, Jacek; Eder, Piotr; Banasiewicz, Tomasz; Matysiak, Konrad; Łykowska-Szuber, Liliana (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Anal fistulas occurring in Crohn’s disease (CD) comprise a risk factor of severe course of inflammation. They are frequently intractable due to various factors such as penetration of the anal canal or rectal wall, impaired wound healing, and immunosuppression, among others. Anal fistulas typical to CD develop from fissures or ulcers of the anal canal or rectum. Accurate identification of the type of fistula, such as low and simple or high and complex, is crucial for prognosis as well as for the choice of treatment. If fistulotomy remains the gold standard in the surgical treatment of the former, it is contraindicated in high and complex fistulas due to possible risk of damage to the anal sphincter with subsequent faecal incontinence. Therefore, the latter require a conservative and palliative approach, such as an incision and drainage of abscesses accompanying fistulas or prolonged non-cutting seton placement. Currently, conservative, sphincter-preserving, and definitive procedures such as mucosal advancement or dermal island flaps, the use of plugs or glue, video assisted anal fistula treatment, ligation of the intersphincteric track, and vacuum assisted closure are gaining a great deal of interest. Attempting to close the internal opening without injuring the sphincter is a major advantage of those methods. However, both the palliative and the definitive procedures require adjuvant therapy with medical measures.